Adherence to follow-up and resource use after abnormal FIT-screening: Evaluation of the Danish colorectal cancer screening program - Jørgensen, Susanne Fogh; Larsen, Pernille Thordal; Erichsen, Rune; Andersen, Berit; Rebolj, Matejka; Njor, Sisse (Endoscopy International Open, 2024)
Background and study aims The effectiveness of colorectal cancer screening programs depends on adherence to surveillance protocols for screening-positive individuals. We evaluated adherence in the Danish population-based screening program and estimated the volume of diagnostic resources required to achieve this adherence.Patients and methods In this register- and population-based study, we included individuals with a positive fecal immunochemical test (FIT) screening from 2014 to 2017 and followed them until mid-2022. All endoscopic, imaging, and surgical procedures performed at public and private hospitals were identified. Adherence to national protocols was reported in terms of proportions and timeliness. Use of diagnostic and surveillance procedures was estimated during a 4-year post-screening period.Results Among 82,221 individuals with a positive FIT test, 84% had a baseline colonoscopy within 1 month. After removal of intermediate or high-risk adenomas, 12% and 6%, respectively, did not have any follow-up. Only ~50% had timely surveillance. Approximately 10% to 20%, depending on their referral diagnosis, did not have a second surveillance colonoscopy. In addition, 12% with a negative colonoscopy had a second colonoscopy within 4 years.Conclusions High adherence to baseline colonoscopy after positive FIT-screening is followed by lower adherence throughout the adenoma surveillance program. Better adherence to the guidelines could potentially improve the effectiveness and efficiency of the screening program.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; CRC screening